Control Strategy of VSG Considering Coordinated Energy Management of PV and ES. (June 2020) - Chen, Zhuo; Zeng, Weidong; Shu, Zhou; Liao, Wei; Lin, Yuyi
Abstract: With the increasing permeability of distributed generation in power system, the problem of weak inertia of distributed generators cannot be ignored. By imitating the mechanical and electromagnetic characteristics of the synchronous generator, the virtual synchronous generator (VSG) has the ability of smooth power output, peak regulation and frequency modulation, and becomes a kind of grid-friendly distributed power supply. However, the traditional VSG coordinates the balance of power supply and demand through the energy storage device (ES), which requires a high capacity of ES. In this paper, a control strategy of VSG considering coordinated energy management of ES and PV is proposed. Through real-time analysis of VSG's power output and the state of ES and PV, dynamic adjustment of power output of PV and virtual characteristics of VSG will be made to realize the coordinated control of PV and ES. This strategy effectively improves the dependence of VSG on ES's capacity by giving priority to the adjustment of PV's power and asymmetric control of ES's SOC.